(untitled) (VETERINARIA, 2020)
Research in this study had the character of retrospective study for which we used 24 adult female Wistar rats, who we reared under standardized laboratory conditions and divided into two groups: experimental and control. The experimental group consisted of a total of 12 animals who were classified into 2 subgroups: Z1 and Z2. The control group consisted of 12 untreated animals who were divided into 2 subgroups: K1 and K2. Once a day at regular intervals we applied by the gastric probe mycotoxin zearalenone previously dissolved in sunflower oil. To the animals in the control group we applied sunflower oil only. Dose of toxin administered was 0,5 mg/kg body weight, and a period of observation spanned two different time intervals-14 and 28 days. After completing the application of toxins, the animals were sacrificed under the general ether anesthesia and by the rules of autopsy techniques. Taken ovaries were prepared for histological and stereological analysis. Structural changes in the ovaries of treated animals were observed as degenerative changes, primarily at the level of the ovarian follicles and corpora lutea. The apparent findings in the stroma were in terms of its hipercelularity and marked hyperemia of the blood vessels. The longer the application period, the more pronounced the changes The resulting qualitative histological changes in the ovaries of treated rats were objectified quantitatively - by stereology. We found changes in terms of decreasing volume density of functional elements of the parenchyma (ovarian follicles and corpora lutea), and increased volume density of ovarian stroma with blood vessels.